Health Benefits of Oats – a review of Cardiovascular, Glycemic, and Gut Effects, and more - Wróbel, Bartosz; Wójcik, Lena; Filipski, Michał; Klonowska, Justyna; Ptaszkiewicz, Kuba; Kosek, Szymon (Quality in Sport, 2026)
Oat (Avena sativa L.), particularly as oatmeal, is distinguished by its high β-glucan content, a soluble dietary fiber with proven therapeutic potential. Meta-analyses and randomized controlled trials confirm that regular intake of oats or β-glucan-enriched products lowers total and LDL-cholesterol without significantly affecting HDL-cholesterol or triglycerides, while also improving anthropometric measures in individuals with mild metabolic disturbances. Additionally, β-glucan slows glucose absorption, reducing postprandial glycemia and long-term glycemic control markers like HbA1c and HOMA-IR in type 2 diabetes patients, as well as stabilizing glucose variability in type 1 diabetes. Oats favourably modulate gut microbiota, boosting short-chain fatty acid (SCFA) production, beneficial bacterial abundance, and intestinal barrier integrity, thereby supporting the gut-metabolism axis. Preliminary data also suggest benefits for satiety, inflammation reduction, and cognitive function. Despite promising results, heterogeneity in β-glucan dose, form, and intervention duration highlights the need for further high-quality studies, including long-term trials with well-characterized oat preparations.